Purpura Fulminans in Neonate: A Case Report - Jahan, Nishat; Saha, Liton Chandra; Bhuiyan, Farhana; Nisha, Samira Islam (Dhaka Shishu (Children) Hospital Journal, 2025)
Abstract not available DS (Child) H J 2023; 39(2): 120-122